Innovating Competency-Based Learning Through Digital Technologies for Sustainable Local Governance in Sarawak - Lee, Jun Choi; Sopian, Bujang; Nadri Aetis Heromi, Basmawi; Ade Syaheda Wani, Marzuki (2025)
Local governments are pivotal in promoting sustainable development through innovation and technology-driven governance. This study examines how the integration of digital innovation into competency-based learning can enhance workforce sustainability and governance readiness within Sarawak’s local councils. Guided by Human Resource Development (HRD) and adult learning perspectives, a mixed-methods design was employed involving 208 officers from 10 local councils. Quantitative assessments measured functional and behavioral competencies, while qualitative insights from focus group discussions identified systemic challenges affecting workforce readiness. Results indicated that officers displayed strong behavioral competencies— particularly communication, teamwork, and cultural sensitivity—reflecting effective interpersonal engagement and social cohesion within councils. However, notable competency gaps emerged in digital literacy, crisis management, sustainability awareness, and innovation practices, signaling limited preparedness for technology-driven governance. These findings underscore the need for HRD reforms that embed digitalized learning mechanisms such as elearning, simulation-based training, and AI-supported competency assessments. In response, this study proposes a Digital Competency-Based Learning (DCBL) model that aligns with Malaysia’s Twelfth Malaysia Plan (Economic Planning Unit, 2021), Sarawak’s Post-COVID Development Strategy 2030 (PCDS 2030), and the United Nations Sustainable Development Goals (SDGs).The model emphasizes the strategic integration of technological innovation into HRD systems as a transformative pathway for cultivating adaptive, ethical, and future-ready governance. Ultimately, the study concludes that leveraging digital innovation within competency-based frameworks is essential for strengthening organizational resilience, promoting sustainable public service delivery, and ensuring that local governments remain agile and responsive in an increasingly digital governance environment.